Estudo da sinterização de compósitos densos de Al₂O₃ contendo inclusões nanométricas de ZrO₂ - Déo, Luciene Cristina Chiari (2009)
The search for materials that posses exceptional hardness, resistance to high temperatures and chemical stability had expanded the areas of application and use of ceramic materials. The development of research about composites containing nanometric inclusions in its matrix increased due to the results of significant improvement in the mechanical properties of composites formed by an alumina matrix with nanometric inclusions of SiC. The mechanisms that enable the improvement of this property have not been fully justified. It was found that the presence of nanometric inclusions delay the beginning of the densification and shrinkage of the samples by raising the temperatura of sintering. This fact was the main motivation for the accomplishment of this work, that had as objective to study the sintering kinetics in the initial stage of alumina samples with and without the presence of nanometric inclusions of zirconia. The study method used was that proposed by Woolfrey and Bannister based on the work of Young and Cutler. With the application of this model, possible mechanisms acting in the system were identified. The samples had been gotten by the desaglomeration of the powders and posterior mixture in mill, isostatic pressing and sintering in dilatometer under constant taxes of heating of 3, 5, 9 and 15 C/min in air, with maximum sintering temperatures of 900, 1000, 1100, 1200, 1300, 1400 and 1500 C. The samples had been characterized how much its apparent density, specific superficial area and microstructure. A change in the mechanism acting in the initial stage of sintering was identified for samples containing nanometric inclusions of zirconia.